Global Poverty : Four Normative Positions - Gauri, Varun; Sonderholm, Jorn (Taylor and Francis, 2013)
Global poverty is a huge problem in today's world. This survey article seeks to be a first guide to those who are interested in, but relatively unfamiliar with, the main issues, positions and arguments in the contemporary philosophical discussion of global poverty. The article attempts to give an overview of four distinct and influential normative positions on global poverty. Moreover, it seeks to clarify, and put into perspective, some of the key concepts and issues that take center stage in the philosophical discussion of global poverty. The four positions to be discussed are labeled the Maximalist Position, the Minimalist Position, Intermediate Position I and Intermediate Position II. After an account of these four distinct positions, we turn, in the conclusion, to a discussion of what role empirical sciences such as economics and political science should play in normative considerations about global poverty.